Microsoft System center configuration manager : high availability and performance tuning : deploy a scalable solution by ensuring high availability and disaster recovery using configuration manager - Sandbu, Marius (Professional expertise distilled., 2013)
Chapter 2: Configuring Roles for High Availability; Site Server; Endpoint Protection; Asset Intelligence Synchronization Point; Fallback Status Point; Out of Band Service Point; Secondary sites; Windows Intune Connector; Management Point; Distribution point; PXE distribution point; Cloud-based distribution point; Pull-based distribution point; Rate limiting options; Application Catalog Website point; Application Catalog Web Service point; Reporting Services point; State Migration point; System Health Validator point; SMS Provider; Software Update point; Client; Sample site designs.